2017
DOI: 10.2106/jbjs.16.00720
|View full text |Cite
|
Sign up to set email alerts
|

Females with Unexplained Joint Pain Following Total Joint Arthroplasty Exhibit a Higher Rate and Severity of Hypersensitivity to Implant Metals Compared with Males

Abstract: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…Examination of retrievals demonstrated that wear of the TiN film may expose the substrate alloy, which could potentially compromise antiallergic properties of the implants; lack of coating in recessed parts of tibial components was another alarming finding (Granchi et al, ; Innocenti et al, ; Lachiewicz et al, ). However, the mechanism of hypersensitivity to metals found in orthopedic implants are poorly understood, and data from the literature is inconclusive whether the exposure observed in our retrievals would have negative consequences for metal sensitive patients (Bravo et al, ; Caicedo et al, ; Kręcisz et al, ). Coating wear and presence of defects could also negatively affect tribological properties of the implants, potentially accelerating polyethylene wear and osteolysis (Wang, Polineni, Stark, & Dumbleton, ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Examination of retrievals demonstrated that wear of the TiN film may expose the substrate alloy, which could potentially compromise antiallergic properties of the implants; lack of coating in recessed parts of tibial components was another alarming finding (Granchi et al, ; Innocenti et al, ; Lachiewicz et al, ). However, the mechanism of hypersensitivity to metals found in orthopedic implants are poorly understood, and data from the literature is inconclusive whether the exposure observed in our retrievals would have negative consequences for metal sensitive patients (Bravo et al, ; Caicedo et al, ; Kręcisz et al, ). Coating wear and presence of defects could also negatively affect tribological properties of the implants, potentially accelerating polyethylene wear and osteolysis (Wang, Polineni, Stark, & Dumbleton, ).…”
Section: Discussionmentioning
confidence: 95%
“…This is because TiN and similar films can act as a barrier protecting the substrate material from corrosion and metal ion release (Corin Group, ; Granchi et al, ; Implantcast GmbH, ; Lachiewicz et al, ; Middleton & Toms, ; Reich et al, ; Thomsen, Rozak, & Thomas, ). The clinical use of such components is the subject of debate, predominantly because immunological mechanisms of metal hypersensitivity in patients with knee replacements are not well understood (Bravo et al, ; Caicedo, Solver, Coleman, Jacobs, & Hallab, ; Granchi et al, ; Lachiewicz et al, ; Middleton & Toms, ). However, several studies suggested that coated implants can reduce the risk of metal sensitization after primary arthroplasties (Bravo et al, ; Granchi et al, ; Innocenti et al, ; Kręcisz, Kieć‐Świerczyńska, & Chomiczewska‐Skóra, ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have found gender differences associated with orthopedic implants, including women having higher sensitivity to the metals found in joint replacements (Caicedo et al. ), and female pediatric patients having worse outcomes after plate implant to repair displaced forearm fracture (Vopat et al. ).…”
Section: Gender and Medical Implant Failuresmentioning
confidence: 99%
“…This finding was not expected at the time, but resonates with more general concerns about the safety and effectiveness of medical devices for women patients. A number of studies have found gender differences associated with orthopedic implants, including women having higher sensitivity to the metals found in joint replacements (Caicedo et al 2017), and female pediatric patients having worse outcomes after plate implant to repair displaced forearm fracture (Vopat et al 2014). Cardiac devices have also been a focus of concern, with evidence that women are less likely than men to benefit from some implantable cardiac devices and more likely to have complications (Dhruva and Redberg 2012).…”
Section: Gender and Medical Implant Failuresmentioning
confidence: 99%
See 1 more Smart Citation